The Role of Paternal Involvement on Behavioral Sensitive Responses and Neurobiological Activations in Fathers: A Systematic Review - Giannotti, Michele; Gemignani, Micol; Rigo, Paola; Venuti, Paola; De Falco, Simona (Frontiers in Behavioral Neuroscience, 2022)
As fathering research has flourished, a growing body of studies has focused on behavioral and neurobiological mechanisms, respectively associated with caregiving sensitivity and responsiveness to infant stimuli. However, the association between these aspects and the key concept of paternal involvement in childcare (i.e., contribution in infant care in terms of time, availability, and responsibility) has been poorly investigated. The current work aims to systematically review the role of involvement in childcare on both neural activations and sensitive behaviors in fathers by examining (a) how paternal involvement has been measured and (b) whether paternal involvement has been associated with neurobiological activation and behavioral sensitive responses. Inclusion criteria were peer-reviewed quantitative studies, concerning fathers responding to infant stimuli at neurobiological or behavioral level, and including a quantitative measurement of paternal involvement in childcare. A quality rating for each study has been performed based on the measurements adopted to assess paternal involvement. Of 2529 articles, 27 studies were included. According to our quality rating, 10 out of 27 studies included fairly good-standard measures for measuring paternal involvement, whereas 17 studies used good-standard measures. In addition, 11 studies provided details of paternal involvement in the context of neurobiological responses to infant stimuli, whereas 16 addressed paternal sensitive behaviors. Overall, only 8 studies reported relevant findings about the relationship between paternal involvement and neurobiological responses or sensitive behaviors in fathers. The present study is the first systematically evaluating the scope of paternal involvement in the field of Paternal Brain and fathers’ sensitive responsiveness research. When high-standard measures are used, paternal involvement seems to play a significant role in modulating both the hormonal and the neural pathways associated with paternal behaviors. Remarkably, the role of paternal engagement may underpin an adaptive nurturance that is not dependent on pregnancy and childbirth but on caregiving experience. A promising positive link between paternal involvement and behavioral sensitivity may be expected in further studies, which will need to corroborate our conclusion by adopting detailed and appropriate measures assessing paternal involvement. As a future line of research, the inclusion of gay fathers may be beneficial for the field.